Hari Suci Tumpek Wariga dan Nilai-Nilai Pendidikan Hindu di Desa Mantaren II Kabupaten Pulang Pisau - Wibawa, Bayu Dwiartha (Satya Widya: Jurnal Studi Agama, 2024)
Tumpek wariga has been implemented for a long time by ethnic Balinese Hindus and is still maintained by ethnic Balinese Hindus who have transmigrated in Mantaren II village. Tumpek wariga is one of the holy days that is routinely celebrated every six months. The holy day is a form of implementation of the values in Hindu teachings contained in the holy book. However, the values of Hindu teachings conveyed through the implementation of tumpek wariga holy day have not been fully understood by Hindus in Mantaren II village. This study intends to explore and understand the values of Hindu Education contained in the implementation of the yadnya of tumpek wariga holy day in Mantaren II village. This study uses a phenomenological qualitative method approach with data collection techniques namely observation, interviews and documents. The data that has been collected is then analysed using the comparative constant technique. The results showed that the implementation of yadnyahari suci tumpek wariga there is a value of Hindu Education namely the value of Tattwa Education, Susila and ceremony.